Ibogaine Blocks Cue- and Drug-Induced Reinstatement of Conditioned Place Preference to Ethanol in Male Mice - Henriques, Gabrielle M.; Anjos-Santos, Alexia; Rodrigues, Isa R. S.; Nascimento-Rocha, Victor; Reis, Henrique S.; Libarino-Santos, Matheus; Barros-Santos, Thaísa; Yokoyama, Thais S.; Bertagna, Natalia B.; Favoretto, Cristiane A.; Moraes, Célia R. G.; Cruz, Fábio C.; et al. (Frontiers in Pharmacology, 2021)
Ibogaine is a psychedelic extracted from the plant Tabernanthe iboga, natural from Africa, and has been proposed as a potential treatment for substance use disorders. In animal models, ibogaine reduces ethanol self-administration. However, no study to date has investigated the effects of ibogaine on ethanol-induced conditioned place preference (CPP). The present study aimed to investigate the effects of repeated treatment with ibogaine on the reinstatement of CPP to ethanol in male mice. The rewarding effects of ethanol (1.8 g/kg, i.p.) or ibogaine (10 or 30 mg/kg, p.o.) were investigated using the CPP model. Furthermore, we evaluated the effects of repeated treatment with ibogaine (10 or 30 mg/kg, p.o.) on the reinstatement of ethanol-induced CPP. Reinstatement was evaluated under two conditions: (1) during a priming injection re-exposure test in which animals received a priming injection of ethanol and had free access to the CPP apparatus; (2) during a drug-free test conducted 24 hours after a context-paired re-exposure, in which subjects received an injection of ethanol and were confined to the compartment previously conditioned to ethanol. Our results show that ethanol, but not ibogaine, induced CPP in mice. Treatment with ibogaine after conditioning with ethanol blocked the reinstatement of ethanol-induced CPP, both during a drug priming reinstatement test and during a drug-free test conducted after re-exposure to ethanol in the ethanol-paired compartment. Our findings add to the literature suggesting that psychedelics, in particular ibogaine, may have therapeutic properties for the treatment of alcohol use disorder at doses that do not have rewarding effects per se.